Risk Factors and Quality of life among Saudi Woman with Reproductive System Cancer - AlEnizi, Miaad AlRawi; Habib, Farida; Afefy, Nagwa Abdel Fadeel (Journal of Language and Health, 2021)
Reproductive cancers have a huge impact in woman quality of life. Research on Saudi Arabian cancer patients is a priority at King Abdulaziz Medical City (KAMC), Riyadh. To date, research on quality of life in cancer patients in Saudi Arabia has been insufficient and there is no enough research that assesses quality of life in gynecological cancer in Saudi women. The aims of this study were to assess the gynecological cancer risk factors and measure the quality of life among Saudi woman who diagnosed with uterine, ovarian or cervical cancer. A descriptive cross-sectional correlational design was used to conduct the study. A convenient sample of 100 Saudi women and who diagnosed with one of reproductive cancer type at King Abdullah Specialized Children Hospital, Riyadh city. Each woman in the sample signed an informed consent to participate in the study. Data was collected using risk factors assessment tool and WHOQOL-BREF questionnaire. Validly and reliability of the questionnaire were ensured. The mean age of the sample was 49.01 Â± 12.88 years, 57 % got menarche at age 13 years, 25% had family history of gynecological cancer, 45% had gotten recurrent genital tract infections, and 47% had an abnormal Pap smear results. There was a statistically significant relationship between the physical health domain and social status (p=0.003), occupation (p=0.000) and monthly income (p=0.040). However, woman psychological health domain was significantly related to occupation n (p=0.000), number of abortions (p=0.001) and menstrual age (p=0.034). It was clear that the age (p=0.024), social status (p=0.011) educational level (p=0.023), and reproductive system hygiene (p=0.005) had significant relationship with woman social relationships domain. Half of the sample had good total quality of life score >70%, while only 11% had poor total quality of life score <50%. This study presented substantial findings that the sample had a moderate quality of life.